Karaktersasi Bakteri Pengurai Plastik Sintetis Polipropilen dari Sampel Air Laut Studi Kasus dan Potensi Lingkungan - Muhammad Diki Juliandi; Akmal Djamaan; Dewi Yudiana Shinta; Anthoni Agustien (Pelantar Press, 2024)
The increase in the number of waste piles in Indonesia has reached 175,000 tons/day or the equivalent of 64 million tons/year. In the health sector, synthetic plastics are used as materials for making packaged medicine bottles and infusion bottles. Polypropylene synthetic plastics are very slow to degrade, making them a major problem in environmental pollution. This study aims to determine the type of bacteria and the ability of bacterial isolates to degrade polypropylene plastics. The research methods used include characterization of bacterial isolates macroscopicly, microscopicly, biochemical tests, then polypropylene synthetic plastic biodegradation tests were carried out during the incubation period of 1 week, 2 weeks, 3 weeks, and 4 weeks using an incubator shaker device. The results of this study obtained 4 bacterial isolates that can decompose polypropylene plastic from seawater samples in Padang City. The results of the isolation of polypropylene plastic bacteria from seawater samples in Padang City ILT-14 bacterial isolate based on macroscopic characteristics. and molecular identification was carried out in the LIPI biotechnology testing laboratory by the 16S rRNA gene deritimization method obtained polypropylene plastic scavenging bacterial species, namely: ILT-14 has similarities with Stenotropomonas Maltophilia. With a 30-day polypropylene plastic decomposer percentage of 10.8%. The difference in FTIR analysis was in the percentage value of carbon group transmission, and the aromatic group decreased. When compared to plastic before it was degraded and there was a decrease in percent. Microscopy Electron Scanning (SEM) Analysis of ILR-14 polypropylene plastic isolate of bacteria isolated is able to break down complex polymers into monomer forms